(untitled) (Research, Society and Development, 2025)
Enteroparasitosis is one of the causes of mortality among children, being triggered by helminths and/or protozoa, as in this age group, children have a developing immune system, therefore, they present the most serious symptoms. The present research aims to verify the presence of parasites in stool samples from children aged 1 to 3 years, enrolled in a CMEI in the municipality of São Pedro do Ivaí- PR. The present investigation analyzed nineteen stool samples that were collected from children aged between 1 and 3 years old and analyzed using microscopic techniques. After analysis using the Hoffman method, it was found that 53% of the samples were positive for intestinal parasites, including Ancylostoma duodenale (31.6%), Giardia lamblia (21.1%) and Entamoeba coli (5.3%). Enteroparasitosis mainly causes malabsorption, chronic diarrhea, anemia, malnutrition and learning difficulties in children, requiring investigation and treatment.